Analysis of Bad Loan Management in Islamic Perspective in Village Owned Enterprises (Case Study in Pakis Putih Village, Kedungwuni District Pekalongan Regency) - Awali, Husni; Santi, Anisah (Tawazuna, 2021)
Along with the development of Islamic Economics in the business world in Indonesia. BUMDes is a microfinance institution that has an important role that aims to improve the economic level of the community, as well as provide funds to the community to develop development in the form of providing credit. The purpose of this study was to determine the factors causing bad loans and how to manage them in an Islamic economic perspective in BUMDes Bina Pakis, Kedungwuni District, Pekalongan Regency. This type of research was conducted with a qualitative descriptive method. Researchers collect data by means of interviews through Social Media such as Whatsapp and Chat Messenger, as well as observations by thoroughly exploring the social situation to be studied. The results of the study can be said that (1) BUMDes "Bina Pakis" Pakis Putih Village, Kedungwuni District, Pekalongan Regency has 75 debtors with a total number of bad loans of Rp. 34,800,000. Since the beginning of BUMDes, bad loans have averaged 12% per year. (2) the causes of bad credit at BUMDes Bina Pakis, namely the tendency to apply for credit funds by customers, there are business constraints, the BUMDes are less thorough in analyzing lending to debtors, and so on. As for when viewed from the perspective of Islamic Economics, in the process of paying credit funds there are delays in payments and breaking promises that have been agreed upon thus violating the provisions in the Word of Allah SWT. in Surah Al-Isra: 34 which contains "the promise must be carried out because there will be accountability". On the other hand, the existence of bad loans will cause the circulation of BUMDes funds to be hampered and have an impact on losses for the BUMDes and the community.